Revitalisasi Dakwah dalam Menghadapi Dampak Negatif Budaya Global di Indonesia - Setiana, Wiryo (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
The changes in various of living domain which caused by globalization, constitute daâwah challange need to anticipated professionally. The daâwah experts, both teoritist and practists musnât stay, they must use all ability, increase their competence associate with global demmand. Among competence need to owned by daâi such as: competence in information technology, internet, LCD, Multimedia Messaging Service (MMS), and so on.